Evaluating potential of diatomite as anti clogging agent for porous asphalt mixture - Mohamed Abdullah, N. A. (Penerbit UTM Press, 2016)
Clogging is a major problem that occurs throughout the service life of porous asphalt due to the open nature of the mixture itself. Diatomite with characteristic of abrasiveness and porous structure seems to have potential in order to remove the clogging materials that mainly consists of soils. This study aims to investigate the effects of diatomite as anti-clogging agent on the permeability rate and strength of porous asphalt. The porous asphalt samples were prepared using Malaysia aggregate gradation and polymer modified bitumen of PG76 was used as the binder. This study focuses on clay as the clogging material at different concentration. A fixed amount of 0.5 g/L diatomite was applied to the porous asphalt samples as an anti-clogging agent prior to clogging cycles. The permeability test and resilient modulus were then conducted at different clogging concentrations (0.5, 1.0, 1.5 g/L) and cycles, with and without diatomite. It was found that samples with diatomite have a higher permeability rate compared to those without any application of diatomite after a few clogging cycles. As the clogging cycles increase, the clogging materials have trapped and filled up the voids in the porous asphalt samples and increase the resilient modulus result.